2022
DOI: 10.3390/biomedicines10112699
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Mitochondrial DNA Copy Number and Increased Expression Levels of Mitochondrial Dynamics-Related Genes in Sjögren’s Syndrome

Abstract: Sjögren’s syndrome (SS) is a chronic autoimmune multifactorial disease characterized by inflammation and lymphocytic infiltration of the exocrine glands. Several studies have highlighted the involvement of oxidative stress in this pathology, suggesting that it could induce mitochondrial dysfunctions. Mitochondria could have a role in inflammatory and immune processes. Since the mitochondrial DNA (mtDNA) copy number could change in response to physiological or environmental stimuli, this study aimed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Mitochondria in salivary glandular epithelial cells show an abnormal structure with increased lymphocyte infiltration. A few studies have focused on the role of mitochondrial metabolites ( 21 ), such as cytochrome c ( 51 ), mtDNA ( 52 ) or ROS, in the immune microenvironment after salivary gland epithelial injury in pSS. In this study, TEM revealed mitochondrial swelling and autophagosome accumulation in scattered lymphocytes and ductal cells of the LSGs of patients with pSS, which is an important finding.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria in salivary glandular epithelial cells show an abnormal structure with increased lymphocyte infiltration. A few studies have focused on the role of mitochondrial metabolites ( 21 ), such as cytochrome c ( 51 ), mtDNA ( 52 ) or ROS, in the immune microenvironment after salivary gland epithelial injury in pSS. In this study, TEM revealed mitochondrial swelling and autophagosome accumulation in scattered lymphocytes and ductal cells of the LSGs of patients with pSS, which is an important finding.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated in animal model of SSc using Caveolin-1 (−/−) null mice that mitophagy was increased in the stromal cells of the dermis along with other signs characterizing changes in the skin in SSc (Castello-Cros et al, 2011). The study in patients with another autoimmune disease, Sjögren's syndrome have shown the decrease of mtDNA copy number and the increase of the expression of genes associated with mitochondrial dynamics in the peripheral blood of patients with Sjögren's syndrome in comparison with healthy subjects (De Benedittis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Benedittis et al observed a significant increase in mitochondrial dynamics-related gene expression in SS patients, specifically in mitochondrial fission and fusion homeostasis, such as mitofusin-1 (MFN1), and mitochondrial transcription factor A (TFAM). Their research suggested a possible involvement of mitochondrial dysfunctions in the pathogenesis of SS [120]. Yoon et al found that mitochondrial double-stranded RNAs (mt-dsRNAs) were elevated in the saliva and tears of SS patients and in the salivary glands of diabetic mice with salivary dysfunction.…”
Section: Sjögren's Syndromementioning
confidence: 99%